A Review of Belt and Bunker Capacity Design and Control for Underground Conveyor Systems - S. Daniel Thompson (Society for Mining, Metallurgy & Exploration, 1996)
In underground coal mining, the specification and control of belt and bunker capacities are complicated by (1) stochastic and intermittent conveyor loading, (2) a limited ability to reduce surge at the mine face, and (3) occasional overlapping of loading from two or more mine faces on the conveyors. Recently, because of longwall mining and other factors, the capacity requirements of most mine conveying systems have risen substantially; as a result, efficient capacity design and control have become important mine planning issues. This paper reviews these design issues and their associated modeling procedures. Design considerations and modeling difficulties are also examined.